Human rights, the Millennium Development Goals, and the future of development cooperation - Nelson, Paul J. (2007)
Examines the distinct approaches to poverty contained in the human rights movement and the Millennium Development Goals. Finds fundamental differences in the two initiatives' conceptual approaches to poverty reduction, in the policy recommendations they support on key social policy issues, and in the social actors they have been able to mobilize.